What Influences a Plastic Surgery Resident to Pursue an Academic Career? - Benjamin A. Mandel, MD; Sharon M. Weber, MD; Karol A. Gutowski, MD; A. Neil Salyapongse, MD; Michael L. Bentz, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. A previous study demonstrated that independent model plastic surgery residents are less likely to pursue a career in academic surgery than those graduating from other surgical fellowships. This study was designed to evaluate whether a significant curriculum change emphasizing academic plastic surgery skills would be significant in influencing a plastic surgery resident’s decision to pursue a career in academic plastic surgery. Methods:. A survey was sent to 30 consecutive graduates of a university plastic surgery residency program. This program had transitioned from a clinically focused independent residency-training model to an integrated model with a new and structured academic emphasis. Respondents who graduated after this transition (“ACADEMIC” n = 19) were compared with those who graduated before (“CLINICAL” n = 9). Results were analyzed using Fisher’s exact test and Wilcoxon rank sum test. Results:. There were a total of 28 respondents (response rate = 93%). A higher percentage of the ACADEMIC group, in contrast to the CLINICAL group reported that they spent time during residency performing clinical research (84% versus 33%, P = 0.013), and that they are currently conducting clinical research in their practices (79% versus 0%, P < 0.001). These graduates were also more likely to have engaged their mentor both regarding professional issues (61% versus 0%, P = 0.016), and as a role model when choosing a career plan (72% versus 17%, P = 0.050). Finally, a higher percentage of the ACADEMIC exposed group entered an academic practice after training (44% versus 0%, P = 0.026). Conclusion:. In a single plastic surgery residency program, the transition to strong academic mentorship with a structured academic educational program focus correlated with an increase in academic careers among program graduates. A proactive academically oriented educational and mentoring environment may help attract residents to careers in academic surgery.